The Rockslide -Debris Avalanche of the May 18, 1980, Eruption of Mount St. Helens — 10th Anniversary Perspectives - Glicken, Harry (Geoscience Canada, 1990)
Summary The massive rockslide-debris avalanche ofthe May 18, 1980, eruption of Mount St.Helens began with a retrogressive failure triggered by the 08:32 PDT earthquake. It depressurized the volcano's magmatic and hydrothermal system and produced a hummocky deposit with a volume of 2.5 km3. Detailed work provides a comprehensive understanding of a previously poorly understood type of event. The deposit consists of relatively intactpieces (block faciès) of the pre-1980 mountain and mixed material (mixed facies) that is primarily rocks from the pre-1980 Mount St.Helens and the 1980 cryptodome. Travelpaths of rockslide blocks are interpreted from a geologic map of the deposit. The material was fractured and dilated during the rockslide, after which grain-to-grain dispersive stress facilitated flow. During transport, the dilated material mixed but significant finematerial was not produced.